The preparation of several 1,2,3,4,5-functionalized cyclopentane derivatives - Kelch, André S.; Jones, Peter G.; Dix, Ina; Hopf, Henning (Beilstein Journal of Organic Chemistry, 2013)
With the goal of eventually synthesizing [5]radialene (3), the still missing member of the parent radialene hydrocarbons, we have prepared the pentaacetates 21 and 31, the pentabromide 29 and the hexabromide 32. In principle these should be convertible by elimination reactions to the desired target molecule.
Keywords: bromination; cyclopentanes; esterification; permethylcyclopentadiene; polyfunctional compounds; radialenes